You may use the alternate method such that:

` (x-4)^2 = 3 => (x-4)^2 - 3 = 0 => (x-4)^2 - (sqrt3)^2 = 0`

You need to convert the difference of squares into a product using the following formula such that:

`a^2 - b^2 = (a - b)(a + b)`

Reasoning by analogy yields:

`(x-4)^2 - (sqrt3)^2 = (x - 4 - sqrt3)(x - 4 + sqrt3)`

Since `(x-4)^2 - (sqrt3)^2 = 0` , then `(x - 4 - sqrt3)(x - 4 + sqrt3) ` `= 0` , hence, you need to solve the following equations such that:

`{(x - 4 - sqrt3 = 0),(x - 4+ sqrt3 = 0):}=> {(x= 4+ sqrt3),(x= 4- sqrt3):}`

**Hence, evaluating the solutions to the given equation yields `x = 4 +sqrt3` and `x = 4 - sqrt3.` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now